Exploring the effect of bag-of-words and bag-of-bigram features on Turkish word sense disambiguation - Adalı, Eşref; İLGEN, BAHAR (My University, 2014)
Feature selection in Word Sense Disambiguation (WSD) is as important as the selection of algorithm to remove sense ambiguity. Bag-of-word (BoW) features comprise the information of neighbors around the ambiguous target word without considering any relation between words. In this study, we investigate the effect of BoW features and Bag-of-bigrams (BoB) on Turkish WSD and compare the results with the collocational features. The results suggest that BoW features yield better accuracy for all the cases. According to the comparison results, collocational features are more effective than both BoW and the BoB features on disambiguation of word senses.
Keywords: Word Sense Disambiguation; feature selection; supervised methods; bag-of-word features